Validation of CORE-Model-Based Geometry Teaching Materials Supported by Wingeom Software - Sri Yulianti; Darhim Darhim; Bambang A.P Martadiputra; Jarnawi Afgani Dahlan (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study aims to evaluate the content validity of geometry teaching materials designed for Grade VII junior high school students. These materials were developed using the Connecting, Organizing, Reflecting, and Extending (CORE) instructional model, supported by Wingeom software, to enhance students' conceptual understanding of geometry. To assess validity, expert validation was conducted using structured questionnaires. Six categories of experts participated: subject-matter experts, media experts, mathematicians, school mathematicians, language experts, and learning evaluation experts. Each category included five experts. The Content Validity Index (CVI) was employed to quantify the degree of agreement among experts regarding the relevance of the materials. The results showed high content validity across all expert groups. Specifically, the s-CVI values were 0.96 for media experts, 0.98 for subject-matter experts, 0.97 for mathematicians, 0.96 for school mathematicians, and similarly high scores for evaluation and language experts. These scores exceed the commonly accepted threshold for strong content validity (s-CVI ≥ 0.90). The high CVI values indicate that the geometry teaching materials are valid in terms of content, language, instructional design, and evaluation components. Consequently, the materials are appropriate for use in further research related to mathematics learning processes at the junior high school level.